Análise dos fatores influenciadores do desempenho acadêmico nos cursos de bacharelado da UNIFAL-MG - Guides, Dennys Roberto (2024)
Understanding the variables that affect academic performance is essential for improving the quality of teaching and learning. This topic represents a global concern that transcends disciplines and educational levels, as academic outcomes have significant implications for students, educators, educational institutions, and society as a Whole. The motivation for this study assumed that student achievement plays a crucial role in shaping educational trajectories and creating opportunities, both at the individual and institutional levels. Numerous investigations have analyzed factors associated with student performance in external environments of Higher Education Institutions (HEIs); however, there is a need to further explore this issue within the internal environment of HEIs, given the scarcity of research in this area at the undergraduate level in Brazil. With the aim of analyzing the factors influencing academic performance in the bachelor's programs at UNIFAL-MG, secondary socioeconomic data were utilized, collected between 2013 and 2023. This is a quantitative study, descriptive and exploratory in nature, conducted with a sample of 4925 graduates, using both parametric and non-parametric inferential statistical techniques. The initial data indicated that the study population has an average age close to 25 years, being predominantly white or mixed-race, with female predominance. Most families were composed of three to five members. The majority of students did not engage in remunerated activity before entering the institution. Parental education levels were concentrated at the fundamental, secondary, and higher education levels. A balance was observed between students from private and public high schools, with the majority residing in the states of Minas Gerais and São Paulo. Additionally, using multiple linear regression models, it was concluded that the academic performance coefficient is positively or negatively related to socioeconomic and sociodemographic variables.